2008
DOI: 10.1177/1744987108089624
|View full text |Cite
|
Sign up to set email alerts
|

Research and practice hand in hand: the experience of promoting research of benefit to people with learning disabilities from within the NHS

Abstract: The paper describes how clinicians from different disciplines and agencies working with children and adults with learning disabilities have joined forces to promote and conduct research pertinent to this client group. Examples of research projects show how practitioners can improve the evidence base and service delivery. Difficulties for practitioners in conducting research and gaining funding are described, with reference to the recommendations of the Cooksey report (2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The findings are promising, and offer potentially improved cut-off scores (Merwood et al, in preparation). Further research professionals have banded together and sought partners in the local universities to foster research with adults and children with developmental disabilities (McBrien, 2008) and this provides valuable support.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are promising, and offer potentially improved cut-off scores (Merwood et al, in preparation). Further research professionals have banded together and sought partners in the local universities to foster research with adults and children with developmental disabilities (McBrien, 2008) and this provides valuable support.…”
Section: Discussionmentioning
confidence: 99%
“…The Adult Down Syndrome Center in Chicago, Illinois, reported that 79% of adults presenting with a decline in mental function had treatable, reversible disorders that have been attributed to Alzheimer's disease (Chicoine & McGuire, ). McBrien () reported that adults with DS will be diagnosed with Alzheimer's disease at younger age, because of rapid aging.…”
Section: Alzheimer's Diseasementioning
confidence: 99%